2011
DOI: 10.1645/ge-2782.1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Sporozoite-Specific Antigen from Toxoplasma gondii

Abstract: Reduction of risk of human and food animal infection with Toxoplasma gondii is hampered by the lack of epidemiological data documenting the predominant routes of infection (oocyst versus tissue cyst consumption) in horizontally transmitted toxoplasmosis. Existing serological assays can determine previous exposure to the parasite, but not the route of infection. We have used difference gel electrophoresis in combination with tandem mass spectroscopy and Western blot to identify a sporozoite-specific protein (To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
128
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(131 citation statements)
references
References 56 publications
0
128
0
3
Order By: Relevance
“…Persons may be unaware of their exposure or may have difficulty recalling specific risks that occurred. The recent discovery of a sporozoite-or oocyst-specific protein, which elicited antibody production and differentiated oocyst-versus tissue cyst-induced experimental infection in pigs and mice, may help to solve this problem (168). Serum antibodies to the sporozoite protein were detected in humans within 6 to 8 months of an initial oocystacquired infection.…”
Section: How Do Humans Become Infected?mentioning
confidence: 99%
“…Persons may be unaware of their exposure or may have difficulty recalling specific risks that occurred. The recent discovery of a sporozoite-or oocyst-specific protein, which elicited antibody production and differentiated oocyst-versus tissue cyst-induced experimental infection in pigs and mice, may help to solve this problem (168). Serum antibodies to the sporozoite protein were detected in humans within 6 to 8 months of an initial oocystacquired infection.…”
Section: How Do Humans Become Infected?mentioning
confidence: 99%
“…Recent findings by Dr. Hill and colleagues using a sporozoite antigen test suggest that the oocyst form of T. gondii, which is associated with soil and cat feces exposure, may be responsible for a majority of human infections in the United States. 22,23 If this is currently the case, one possibility is that some of the reduction in human exposure to T. gondii in the past 20 years was caused by a reduction of T. gondii in meats such as pork, which has been documented, 24 or less exposure from meat in general because of changes in preparation or freezing practices. An increase in frozen pre-prepared meals and freezing of meat helps reduce exposure to infectious T. gondii cysts because cysts are inactivated by adequate freezing.…”
Section: Discussionmentioning
confidence: 99%
“…53 Recent studies suggested that oocysts were the predominant route of transmission of T gondii infections in the United States; 78% (59 of 76) of pregnant women with acute primary T gondii infections during pregnancy who gave birth to infants with CT had serologic evidence suggestive of being infected by oocysts. 23,54 Different types of locally produced meat from retail meat stores in the United States (eg, pork, lamb, goat, wild game meat) have been found to be contaminated with T gondii. 39, 46, 56 -59 Moreover, with the globalization of the food market, imported meats from other countries (that could be infected even with atypical, more virulent T gondii strains) also can be found in the United States and Europe.…”
Section: Routes Of Transmission and Risk Factors For T Gondii Infectionmentioning
confidence: 99%